Palladium-Catalyzed Asymmetric Diene Cyclization/Hydrosilylation Employing Functionalized Silanes and Disiloxanes - Pei, Tao; Widenhoefer, Ross A (Journal of organic chemistry, 2001)
Pentasubstituted disiloxanes and silanes of the form HSiMe2CH x Ph3 - x (x = 1 or 2) reacted with dimethyl diallylmalonate (1) and other functionalized 1,6-dienes in the presence of a catalytic 1:1 mixture of (N−N)Pd(Me)Cl [N−N = (R)-(+)-4-isopropyl-2-(2-pyridinyl)-2-oxazoline] [(R)-2] and NaBAr4 [Ar = 3,5-C6H3(CF3)2] to form the corresponding silylated cyclopentanes in good yield with high diastereoselectivity. The enantioselectivity of cyclization/hydrosilylation of 1 with disiloxanes and functionalized silanes at −20 °C increased in the following order:  HSiMe2OSiMe3 (75% ee) < HSiMe2OSiMe2-t-Bu (80% ee) < HSi(i-Pr)2OSiMe3 (86% ee) = HSiMe2Bn (86% ee) < HSiMe2OSi(i-Pr)3 (89% ee) < HSiMe2OSiPh2-t-Bu (91% ee) < HSiMe2CHPh2 (93% ee). Silylated cyclopentanes derived from HSiMe2OSiMe3 were oxidized with excess KF and peracetic acid at room temperature for 48 h to form the corresponding hydroxymethylcyclopentanes in good yield (82−95%). Silylated cyclopentanes derived from HSiMe2OSiPh 2 t-Bu were oxidized with a mixture of tetrabutylammonium fluoride and either H2O2 or peracetic acid to form the corresponding alcohols in 48−76% yield. Silylated carbocycles generated from benzhydryldimethylsilane were oxidized with a mixture of TBAF/KHCO3/H2O2 in 71−98% yield. Asymmetric cyclization/hydrosilylation/oxidation employing benzhydryldimethylsilane tolerated allylic and terminal olefinic substitution and a range of functional groups.